Identifying rapidly parasiticidal anti-malarial drugs using a simple and reliable in vitro parasite viability fast assay. (December 2015) - Linares, María; Viera, Sara; Crespo, Benigno; Franco, Virginia; Gómez-Lorenzo, María; Jiménez-Díaz, María; Angulo-Barturen, Íñigo; Sanz, Laura; Gamo, Francisco-Javier
Abstract Background The emergence ofPlasmodium falciparum resistance to artemisinins threatens to undermine the effectiveness of artemisinin-based combination anti-malarial therapy. Developing suitable drugs to replace artemisinins requires the identification of new compounds that display rapid parasite killing kinetics. However, no current methods fully meet the requirements to screen large compound libraries for candidates with such properties. This study describes the development and validation of an in vitro parasite viability fast assay for identifying rapidly parasiticidal anti-malarial drugs. Methods Parasite killing kinetics were determined by first culturing unlabelled erythrocytes withP. falciparum in the presence of anti-malarial drugs for 24 or 48 h. After removing the drug, samples were added to erythrocytes pre-labelled with intracellular dye to allow their subsequent identification. The ability of viable parasites to re-establish infection in labelled erythrocytes could then be detected by two-colour flow cytometry after tagging of parasite DNA. Thus, double-stained erythrocytes (with the pre-labelled intracellular dye and the parasite DNA dye) result only after establishment of new infections by surviving parasites. The capacity of the test anti-malarial drugs to eliminate viable parasites within 24 or 48 h could, therefore, be determined. Results The parasite viability fast assay could be completed within 48 h following drug treatment and distinguished between rapidly parasiticidal anti-malarial drugsversus those acting more slowly. The assay was validated against ten standard anti-malarial agents with known properties and results correlated well with established methods. An abbreviated assay, suitable for adaption to medium–high throughput screening, was validated and applied against a set of 20 compounds retrieved from the publically available Medicines for Malaria Venture 'Malaria Box'. Conclusion The quantification of new infections to determine parasite viability offers important advantages over existing methods, and is amenable to medium–high throughput screening. In particular, the parasite viability fast assay allows discrimination of rapidly parasiticidal anti-malarial candidates.